2013
DOI: 10.1039/c3dt52079j
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the synthetic chemistry of technetium disulfide

Abstract: Technetium disulfide was prepared by reaction between the elements in a sealed tube at 450 °C, by reaction between Tc2(O2CCH3)5 and H2S gas in a flowing system at 450 °C and by reaction between K2TcCl6 and H2S gas in sulfuric acid. The samples were analysed by X-ray absorption fine structure (XAFS) spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In our system, the Tc K ‐edge shift was consistent with the presence of a Tc IV species (shift of –6.5 to –10.5 eV relative to TcO 4 – ). As suggested in a previous study, the position of the Tc K ‐edge is lower in TcS 2 than in TcO 2 due to the difference in electronegativity between O and S ligands 4. Based on the presented data and discussed literature, the existence of a Tc VII species with the formula Tc 2 S 7 is considered unlikely.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…In our system, the Tc K ‐edge shift was consistent with the presence of a Tc IV species (shift of –6.5 to –10.5 eV relative to TcO 4 – ). As suggested in a previous study, the position of the Tc K ‐edge is lower in TcS 2 than in TcO 2 due to the difference in electronegativity between O and S ligands 4. Based on the presented data and discussed literature, the existence of a Tc VII species with the formula Tc 2 S 7 is considered unlikely.…”
Section: Resultssupporting
confidence: 53%
“…Concerning technetium binary sulfides, only two compounds have been reported: TcS 2 and Tc 2 S 7 . Only technetium disulfide has been unambiguously characterized 2,4. Even though colloidal technetium heptasulfide is used in radiopharmaceuticals applications,5,6 and has been proposed as an immobilization process for environmental technetium,7 its exact structure and composition are still unclear 8,9…”
Section: Introductionmentioning
confidence: 99%
“…Study of the TcS 2 has always been hampered by the small quantities of materials yielded by traditional synthesis routes. Three new synthesis routes for TcS 2 were also recently reported (Ferrier et al, 2013). These new synthesis routes allow one to obtain larger yields of technetium sulfides at lower temperatures.…”
Section: Technetium Sulfidesmentioning
confidence: 99%
“…Three new synthesis routes for TcS 2 were also recently reported. 27 These new synthesis routes allow one to obtain larger yields of technetium sulfides at lower temperatures. More routine synthesis of larger batches of TcS 2 will lead to better experiments exploring the efficacy of using TcS 2 as a waste form (see below).…”
Section: Technetium Sulfidesmentioning
confidence: 99%
“…Previous studies have also shown that pertechnetate can be readily bioreduced to Tc(IV)O 2 ⋅ x H 2 O (Istok et al, 2004; Fredrickson et al, 2009), a precipitate that can be quickly and nearly completely reoxidized. In contrast, Tc(IV) precipitated with sulfide (TcS 2 or TcS x ) oxidizes more slowly (Livens et al, 2004; Lukens et al, 2002, 2005; Ferrier et al, 2013). In addition, Tc(IV) incorporates into slower dissolving phases including Fe sulfides (Fan et al, 2013), sodalite (Wharton et al, 2000), and goethite (Livens et al, 2004).…”
mentioning
confidence: 99%